Amplified Electrochemical Aptasensor for Sialic Acid Based on Carbon‐Cloth‐Supported Gold Nanodendrites and Functionalized Gold Nanoparticles. Issue 4 (16th January 2020) - Lv, Yubing; Zhou, Yanli; Dong, Hui; Liu, Lantao; Mao, Guoliang; Zhang, Yintang; Xu, Maotian
Abstract: The abnormal expression of sialic acid (SA) on the cell surface or in bodily fluids has been proven to correlate with several diseases. An electrochemical approach has been developed for the sensitive and accurate determination of SA in human serum samples. Gold nanodendrites (AuNDs) electrodeposited on a carbon cloth (CC) electrode were utilized as the substrate electrode and provided high surface area and conductivity. The thiolated nucleic acid aptamer of SA was immobilized and recognized SA specifically, followed by the attachment of the nanocomposite of gold nanoparticles with 4‐mercaptophenylboric acid and thionine (MPBA−AuNP−Th) via boronic acid‐diol binding. An amplified signal by the electrochemical reduction of Th could be obtained because of high conductivity of substrate and high loading of Th on AuNPs. The proposed sensor exhibited remarkable selectivity and high sensitivity with a low detection limit of 60 nM, owing to the high affinity of aptamer and the signal amplification strategy, respectively. The feasibility of the aptasensor was verified by evaluation of SA level in human serum. Abstract : Time to dual : An aptasensor assay for the detection of sialic acid is developed based on dual signal amplification by carbon‐cloth‐supported Au nanodendrites (AuNDs/CC) and functionalized Au nanoparticles (AuNPs). The AuNDs/CC film provides plentiful binding sites for aptamers. The captured SA is attached by the boronic‐acid‐modified AuNP conjugates featuring thionine. This sensor exhibits remarkable selectivity and high sensitivity.